Analysis of Heat Transfer Performance in a Brayton Cycle Recuperator (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Thermodynamic cycles are currently the most wanted means of converting nuclear power into available work due to the higher conversion efficiencies provided. Rankine cycles have been greatly applied for terrestrial reactors and nuclear submarines, while a lot of space projects have been using Brayton cycles for power conversion mainly due to mitigation in power-to-radiator area ratio. Regenerative Brayton cycles can present a considerable power conversion efficiency improvement when compared to the regular ones because of a reduction on the power demand from the hot heat exchanger of a cycle to achieve the same net output power. In this work, a cross-flow heat exchanger with He-Xe (40 g/mol) working fluid and Inconel 617 structural material used as the recuperator for the closed Brayton cycle of a nuclear reactor applicable for space systems is assessed in terms of heat transfer performance. The recuperator tubes are arranged in a staggered distribution around the exchanger axis. The matrix of tubes has a fixed count of 4 rows along the exchanger axis, while the number of tubes around the axis is variable, where the samples of 5, 7, 9, 12 and 16 are tested. The characteristic curves of heat transfer rate, effectiveness, convection coefficient and Colburn factor are built for each of the studied geometries in function of the Reynolds number. The obtained values for each of these parameters range between 1892.49 and 8493.21W (heat transfer rate), 0.165 and 0.325 (effectiveness), 60.3822 and 176.9682 W/m2K (cold side convection coefficient), 30.3276 and 104.3263 W/m2K (hot side convection coefficient), 0.0071 and 0.0109 (cold side Colburn factor), 0.0523 and 0.1370 (hot side Colburn factor).